Temptations of the West : How to be Modern in India, Pakistan, Tibet and Beyond - Mishra, Pankaj (New York Farrar, Straus and Giroux, 2006)
"In his fourth book, following the acclaimed An End to Suffering, Pankaj Mishra brings literary authority and political insight to bear on journeys that are at once epic and personal." "Traveling in the changing cultures of South Asia, Mishra sees the pressures - the temptations - of Western-style modernity and prosperity, and adroitly teases out the paradoxes of globalization. A visit to Allahabad, the birth-place of Jawaharlal Nehru, occasions a brief history of the tumultuous post-independence politics Nehru set in motion. In Kashmir, just after the brutal killing of thirty-five Sikhs, he sees Muslim guerrillas playing with Sikh village children while the media ponder a (largely irrelevant) visit by President Clinton. And in Tibet he exquisitely parses the situation whereby the Chinese government - officially atheist and strongly opposed to a free Tibet - has discovered that Tibetan Buddhism can be "packaged and sold to tourists.""--
Keywords: Mishra, Pankaj -- Civilization--Western influences -- Travel